(untitled) (Journal of Comparative & International Higher Education, 2021)
Since the 1970s, international students have represented a growing proportion of the global student body, yet how they adjust and how universities can support them is relatively unexplored. We conducted a qualitative study of 36 international students of 11 nationalities studying in Norway and the UK and found that their experience did not fit the dominant ‘U-Curve’ of adaptation that suggests there is a honeymoon period on arrival. Confirmed with conversations with student wellbeing staff, who suggest that anxiety and culture shock are the norm, the data allows us to suggest factors that trigger adjustment and interventions to improve students’ experience. Our contribution is a ‘J-Curve’ model comprising cultural challenge, adjustment, and mastery, to reflect the reality of the international student experience.